Rational Use of Water Resources (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Effective reclamation and water management plays significant role in fostering the economic growth of a country. Water, as a vital natural resource, is important in strategic enhancement of water management practices and the revitalization of irrigated lands to optimize resource utilization and sustainably support economic development.